“Sustainable Optimization of Construction and Demolition Waste Using 5 R Principles” - Komal R. Kaushik (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The global rise of Generation plant and demolition waste the consequence of urbanisation and infrastructures activities has become a major issue in the modern world. Furthermore, wasting natural resources and polluting our environment is caused by the disposal of the wastes in an unsystematic way. It is highly essential to manage the construction and demolition waste properly to save the environment and conserve natural resources. The present study aims to sustainable optimization of construction and demolition waste. The article examines the impacts of 5R principles on sustainable optimization of construction and demolition waste. The study looks through the various waste management techniques of the construction industry. At the same time, also ensures sustainability. The construction sector develops residential, educational, and infrastructure schemes and plans to maintain the socio-economic structure of a country. But, excessive construction generates huge bulk of hazardous and non-hazardous wastes. Scientists are implementing several methods and techniques to optimize waste disposal in an eco-friendly manner. This research will be useful for the policymakers as well as the scholars for further research. DOI: https://doi.org/10.17762/ijisae.v11i11s.8298